2013
DOI: 10.1002/jmri.24534
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of apparent diffusion coefficient value with prognostic parameters of endometrioid carcinoma

Abstract: The minimum ADC correlates with prognostic parameters of endometrial carcinoma more strongly than mean ADC. Lower minimum ADC is associated with higher histological tumor grade and higher degree of myometrial invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
40
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 44 publications
6
40
1
Order By: Relevance
“…Previous studies have also shown a correlation between DTI parameters and tumor histologic grades in cerebral gliomas, breast cancer, and renal cancer; specifically, FA values tended to be lower with greater grade of malignancy, and this tendency may be due to intratumoral heterogeneity and higher cellular density . Previous studies have shown that differentiating among histologic grades of EMCs based on conventional ADC values is often difficult because of the considerable overlap among these values . Therefore, our data support the observation that DTI is more accurate than conventional DWI for differentiating among histologic grades of carcinomas.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous studies have also shown a correlation between DTI parameters and tumor histologic grades in cerebral gliomas, breast cancer, and renal cancer; specifically, FA values tended to be lower with greater grade of malignancy, and this tendency may be due to intratumoral heterogeneity and higher cellular density . Previous studies have shown that differentiating among histologic grades of EMCs based on conventional ADC values is often difficult because of the considerable overlap among these values . Therefore, our data support the observation that DTI is more accurate than conventional DWI for differentiating among histologic grades of carcinomas.…”
Section: Discussionsupporting
confidence: 87%
“…However, accurate preoperative assessment of these prognostic factors is often difficult using conventional MRI. More important, although the histologic grade correlates with other prognostic factors and provides critical information for selecting treatment plans, accurately predicting histologic grade without a needle biopsy remains challenging …”
mentioning
confidence: 99%
“…Minimum ADC (ADC min ) represents the highest tumor cellularity. Studies have shown that both SUV max derived from PET/CT and ADC min of the primary tumor of endometrial cancer are associated with pathological prognostic factors and are independent predictive factors for disease recurrence, whereas SUV max has also been shown to be an independent prognostic factor for overall survival …”
mentioning
confidence: 99%
“…When compared to benign lesions, malignant tumors show higher cellularity, and thereby lower ADC min and higher SUV max values (23,24). Although various studies suggested a possible relationship between the SUV max and ADC min of the primary tumor and tumor characteristics such as grade, myometrial invasion, stage, recurrence, and survival (13,14,25,26,27), uncertainty remains regarding the true magnitude and structure of these relationships as there are limited data that compare both parameters in the same study group.…”
Section: Discussionmentioning
confidence: 99%